Fire effects on Atlantic Forest sites from a composition, structure and functional perspective - Carvalho, L. Z.G. [UNESP]; Massi, K. G. [UNESP]; Coutinho, M. P.; Magalhães, V. D. (FapUNIFESP (SciELO), 2022)
Recently, some portions of the Atlantic Forest biome have been suffering an increase in forest fires, possibly changing its vegetation cover, composition, structure and functioning. Understanding these changes is critical to evaluate the present and future response of tropical forests to fire. Thus, the purpose of our study was to evaluate how diversity, structure and functioning of tree communities differed between burned and unburned sites. Two unburned and two burned forest patches were selected for floristic and phytosociological surveys. Then, we calculated species richness, Shannon diversity index, tree density and basal area, Importance Value Index for trees in each site and we assessed community weighted mean of six functional traits (maximum tree height, wood density, leaf length, leaf deciduousness, shade tolerance and dispersal mode). Diversity, species richness, tree density and basal area were similar between sites. We found changes in floristic composition, but did not verified variations in functional traits. Results indicate that recovery may be fast and that pioneer and early secondary species are occupying post burned sites (nine years old). One-time anthropogenic, superficial and low intensity fires might disrupt advanced stages of succession and start again the dynamics of species substitution.
Efeitos do fogo na Mata Atlântica por meio de uma abordagem de composição, estrutura e funcional
Keywords: burning; diversity; flora; functional traits; tropical rainforest